Roma activism : reimagining power and knowledge - Beck, Sam; Ivasiuc, Ana (Romani studies (Berghahn Books) ;, 2020)
"Exploring contemporary debates and developments in Roma-related research and forms of activism, this volume argues for taking up reflexivity as practice in these fields, and advocates a necessary renewal of research sites, methods, and epistemologies. The contributors gathered here - whose professional trajectories often lie at the confluence between activism, academia, and policy or development interventions - are exceptionally well placed to reflect on mainstream practices in all these fields, and, from their particular positions, envision a reimagining of these practices."--Provided by publisher.